Assessment of psychosocial problems among HIV positive individuals attending in the Teaching Institutes of West Bengal and Bihar, India - Suparna Chatterjee; Panchali Datta; Sumit Datta; Amrita Ghosh; Gautam Sarker; Ranabir Pal (Al Ameen Medical College, 2018)
Background: HIV infection has a chronic course and long-term involvement associated with social stigma in India leading to serious psychological problems manifesting as depression, loss of insight, agitation, insomnia which are remain undiagnosed and untreated. Objectives: This study was done to assess psychological problems among HIV positives. Methods: A cross sectional observational study was conducted on 180 patients who were on anti-retroviral therapy selected through systematic random sampling technique in two Teaching Institute of West Bengal and Bihar. Hamilton Rating Scale for Depression and Anxiety for Psychological problems was used to measure the psychological problems. Results: The study group had 64.44 percent males, among males maximum (56.03%) were between 30-40 yrs. Among females, majority (48.44%) were from age 18-29 years. Among males, 65.52 percent were married followed by divorced (27.59%). Among females, 59.44 percent were married followed by widowed (37.5%). Among the participants majority had education up to secondary level. Depression was more common among females (76.56%) compared to males (53.45%); Insomnia was more frequent finding (83.3%) among separated; Illiterates showed lower frequency of depression. Substance abuse was not associated with insomnia. Conclusions: Identification of psychological problems is important for a better outcome of people living with HIV/AIDS.